2018
DOI: 10.1063/1.5041381
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb explosion imaging of CH3I and CH2ClI photodissociation dynamics

Abstract: The photodissociation dynamics of CH 3 I and CH 2 ClI at 272 nm were investigated by time-resolved Coulomb explosion imaging, with an intense non-resonant 815 nm probe pulse. Fragment ion momenta over a wide m/z range were recorded simultaneously by coupling a velocity map imaging spectrometer with a pixel imaging mass spectrometry camera. For both molecules, delay-dependent pump-probe features were assigned to ultraviolet-induced carbon-iodine bond cleavage followed by Coulomb explosion. Multi-mass imaging al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 65 publications
5
49
0
Order By: Relevance
“…However, though improving the readout speed of the PImMS camera is still a work in progress, the multimass imaging capability is attractive enough that a number of different research groups around the world have already used the camera to perform ultrafast pumpprobe VMI experiments. These include initial proof-of-concept experiments on C2F3I, carried out by Hockett and coworkers at the NRC in Ottawa 47 , and a series of investigations into the photofragmentation and Coulomb explosion dynamics of various alkyl and aryl halides, performed by Rolles and coworkers at the FLASH free electron laser facility in Hamburg 48,49,50,51 . While the experimental methodology still needs further development in order to exploit the approach to its full potential, these early studies have demonstrated that ultrafast time-resolved multimass VMI offers a powerful tool for investigating wavepacket dynamics on the femtosecond timescale, allowing the dynamics of multiple competing reaction channels to be resolved.…”
Section: Ultra-fast Pump-probe Experimentsmentioning
confidence: 99%
“…However, though improving the readout speed of the PImMS camera is still a work in progress, the multimass imaging capability is attractive enough that a number of different research groups around the world have already used the camera to perform ultrafast pumpprobe VMI experiments. These include initial proof-of-concept experiments on C2F3I, carried out by Hockett and coworkers at the NRC in Ottawa 47 , and a series of investigations into the photofragmentation and Coulomb explosion dynamics of various alkyl and aryl halides, performed by Rolles and coworkers at the FLASH free electron laser facility in Hamburg 48,49,50,51 . While the experimental methodology still needs further development in order to exploit the approach to its full potential, these early studies have demonstrated that ultrafast time-resolved multimass VMI offers a powerful tool for investigating wavepacket dynamics on the femtosecond timescale, allowing the dynamics of multiple competing reaction channels to be resolved.…”
Section: Ultra-fast Pump-probe Experimentsmentioning
confidence: 99%
“…The presence of heavy I atoms makes it well suited for diffractive measurements since the scattering cross section is large, providing a high signal-to-noise ratio (SNR). Finally, while the photoproducts have been studied in some detail with nanosecond laser work [57][58][59][60][61][62][63][64][65][66][67], the femtosecond dynamics following deep UV photoexcitation have not been studied in such detail.…”
Section: Introductionmentioning
confidence: 99%
“…Under ideal conditions the probe laser would strip a sufficient number of electrons from the sample molecule to cause it to explode into atomic ions, the so-called 'pure Coulomb explosion' regime. We have demonstrated this approach in our previous work on substituted methanes, bromines, and biphenyl molecules 13,[29][30][31][32] . These earlier experiments employed traditional 'crushed' velocity-map imaging, and we were therefore limited to recording two-dimensional projections of the velocity distributions.…”
mentioning
confidence: 94%